Echinomycin Suppresses the Pyrogenic Effects of Endotoxin and Interleukin- lβ in Human Endothelial Cells and Peripheral Blood Mononuclear Cells - Herbert, Jean-Marc; Lalé, Alain; Pereillo, Jean-Marie; Derocq, Jean-Marie; Casellas, Pierre (Thrombosis and Haemostasis, 1996)
Endotoxin (LPS) and interleukin-1(3 (IL-iβ) increased in a dose-dependent manner the expression of tissue factor, an ubiquitous membrane-anchored glycoprotein that initiates blood coagulation at the surface of human umbilical vein endothelial cells (HUVEC) and human peripheral blood mononuclear cells (PBMC). Echinomycin, a cyclic octapeptide of microbial origin strongly inhibited LPS- and IL-1β-induced tissue factor expression in HUVEC and PBMC with IC50 values in the subnanomolar range at the same time it reduced LPS and IL-iβ-induced expression of intercellular adhesion molecule-1 (ICAM-1, CD54) on HUVEC (IC50 = 0.4 ± 0.1 and 0.3 ± 0.2 nM respectively). Echinomycin also reduced LPS-induced secretion of IL-iβ and IL-6 by human PBMC (IC50 = 10 ± 2 and 3 ± 0.5 nM respectively). These observations demonstrate that echinomycin protects endothelial cells and PBMC from the pyrogenic effect of LPS and 1β.